2020
DOI: 10.1364/ao.386162
|View full text |Cite
|
Sign up to set email alerts
|

Resolution-improved SPR sensor with a rotational modulation method

Abstract: A resolution-improved prism coupler-based surface plasmon resonance (SPR) sensor with a simple, effective rotational modulation method is proposed in this paper. For a conventional SPR sensor, the way to improve its measurement resolution is usually to use the rotating device with higher resolution. Measurement resolution depends on the modulation resolution of the incident angle; therefore, we propose a rotational modulation method that is implemented by rotating the prism horizontally to improve the modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It was observed that the adsorption of the analyte molecules based on carbon with graphene π-bond can enhance the SPR sensor performance. To enhance the performance of biosensors, graphene or molybdenum disulphide (MoS 2 ) can be inserted between the affinity and the metal layers [12,13]. Graphene is a two-dimensional graphite substance with a one-atom thickness that is organized in a honeycomb lattice.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the adsorption of the analyte molecules based on carbon with graphene π-bond can enhance the SPR sensor performance. To enhance the performance of biosensors, graphene or molybdenum disulphide (MoS 2 ) can be inserted between the affinity and the metal layers [12,13]. Graphene is a two-dimensional graphite substance with a one-atom thickness that is organized in a honeycomb lattice.…”
Section: Introductionmentioning
confidence: 99%
“…For small-molecule detection, excessively high precision control and expensive equipment are required to analyze the ultratiny angular or wavelength shift, and this consequently diminishes their access extensively. 29,30 Therefore, some researchers turn to focus on introducing different nanomaterials, such as nanoparticles and graphene, 31−38 as the enhancer to improve the sensitivity toward small molecules. The concept of introducing an enhancer to the analytical method has been used for years in Raman vibrational spectra (surface-enhanced Raman spectroscopy, SERS) for small molecules detection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Most applications of SPR are on the measurement of relatively larger biomolecules, such as antibodies and antigens. However, in recent drug developments, small biomolecules such as oligonucleotides and peptides have had an up-and-coming role in genetic disease testing (e.g., food-borne diseases, HIV, and COVID-19) and drug developments. Given the ultrasmall refractive index change from those small biomolecules, detecting low concentrations of small biomolecules no matter by either the conventional SPR or nanostructure-based Fano resonance is yet challenging. For small-molecule detection, excessively high precision control and expensive equipment are required to analyze the ultratiny angular or wavelength shift, and this consequently diminishes their access extensively. , Therefore, some researchers turn to focus on introducing different nanomaterials, such as nanoparticles and graphene, as the enhancer to improve the sensitivity toward small molecules. The concept of introducing an enhancer to the analytical method has been used for years in Raman vibrational spectra (surface-enhanced Raman spectroscopy, SERS) for small molecules detection.…”
Section: Introductionmentioning
confidence: 99%
“…Surface plasmon resonance (SPR), a subset of surface plasmons (SPs), exhibits a wide range of unique optical features, including varying resonant frequencies in host media with varying refractive indices. Many practical applications in biosensors to detect and characterize chemical and biological substances have been discovered due to SPR's unique optical features [1][2][3][4][5][6]. SPR-based sensors show many advantages such as high reliability and real-time analysis with high sensitivity [7].…”
mentioning
confidence: 99%